Profit volatility and macroeconomic policy adjustments in Rwanda’s real estate sector - Oyasor, Emmanuel Imuede (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
Rwanda’s real estate sector has experienced robust growth in recent years; however, developers continue to face unstable profit margins due to unpredictable macroeconomic policy shifts. This financial volatility undermines investment confidence and sectoral planning. The objective of this study is to examine how macro-policy realignments, specifically interest rate fluctuations, fiscal incentives, and regulatory changes, affect the cyclicality of profit margins among real estate developers in Rwanda. The study employs correlational research design, using secondary data collected from monetary policy bulletins, fiscal records, and audited financial statements of real estate firms between 2019 and 2023. Findings reveal that interest rate changes have a statistically significant and positive effect on profit margin variation, confirming that monetary tightening increases financial uncertainty and compresses returns. In contrast, fiscal incentives and regulatory reforms exhibit statistically insignificant effects, suggesting that these instruments are either poorly structured, inconsistently applied, or too recent in implementation to produce stabilizing outcomes. The study concludes that macroeconomic policy realignments substantially influence profit margin cyclicality, with monetary policy having the most immediate and measurable impact. Accordingly, it recommends that the National Bank of Rwanda institutionalize structured stakeholder consultations before major interest rate decisions to promote risk mitigation, planning certainty, and sustainable sectoral growth.